Geological and Geotechnical Challenges Faced during Excavation of the Underground Powerhouse and Head Race Tunnel for Mangdechhu Project, Bhutan, India - Mishra, A. K.; Chaudhary, R. K.; Punetha, P.; Ahmed, I. (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
Not available. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 23 Year: 2018